generic, DisCourse, and lexicogrammatical Characteristics of a listening exercise in an EFL Classroom - Sagre, Anamaría; Herazo, José David (Íkala, Revista de Lenguaje y Cultura, 2015)
This paper describes the listening exercise as a textual genre of the EFL classroom. To this end, we analyzed a 30-minute listening activity in terms of its purpose, its discourse structure, and the lexicogrammatical choices in EFL of teacher and students. Findings reveal that the discourse structure and lexicogrammatical choices teacher and students made facilitated comprehension and created opportunities for meaningful EFL production, reaching the genre’s purpose. Whereas students were able to understand the listening text thanks to those choices, they were less successful in reporting what they heard and expressing opinions in EFL. This was due, in part, to how the comprehension task was realized linguistically and to the fact that little modeling was provided to express such functions.